2017
DOI: 10.1055/s-0043-114864
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Overuse Injuries in Youth Team Sports: A 3-year Prospective Study

Abstract: Prospective studies on overuse injuries and their impact on athletic training among youth team sports are scarce. The purpose of this study was to investigate the incidence, severity and player related risk factors of overuse injuries among young (12-20 years) basketball and floorball players. A total of 387 players participated in a 3-year prospective study. Each player completed a baseline questionnaire regarding their background information. Overuse injuries that prevented players to fully or partly partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 63 publications
3
53
1
2
Order By: Relevance
“…Furthermore, the older players sustained four to five times as many lower back problems. Low back pain has been reported to be common in other youth team sports as well,44 and in a growing athlete it is related to a high prevalence of structural pathology, such as spondylolysis 45…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the older players sustained four to five times as many lower back problems. Low back pain has been reported to be common in other youth team sports as well,44 and in a growing athlete it is related to a high prevalence of structural pathology, such as spondylolysis 45…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies reported overuse injuries of the elbow and/or shoulder as outcome measure. These studies were published between 1997 and 2017 in the USA, Australia, Norway, Finland, the Netherlands, and Luxembourg . Four studies collected data prospectively, while the other studies had a retrospective study design …”
Section: Resultsmentioning
confidence: 99%
“…The eight studies that reported overuse as outcome measure reported injuries in baseball, softball, basketball, handball, volleyball, and tennis . Three studies described overuse injuries in more than one sport, and three studies focused on elite athletes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The American Medical Society for Sports Medicine made a position statement concerning repetitive injuries and burnout, which are common problems in sports. (DiFiori et al, 2014) According to Leppanen et al (2017), there are multiple causes for sports injuries and, depending on the sport, some parts of the athlete's body is more likely to be injured, and the number of athletes getting injured is increasing. Drawing from this finding, we decided to carry out the present research, under the title "The Most Common Injuries Among Jordanian Wheelchair Athletes".…”
mentioning
confidence: 99%